Social networks and health - Levy, Judith A.; Pescosolido, Bernice A. (Advances in medical sociology ;, 2002)
This volume is directed toward researchers and health professionals with an interest in the interstices of social networks and health. It consists of original papers that address critical themes in health-related social network research and disease prevention. The sections discuss the dynamics of social networks and their role in providing social support under varying conditions and contexts; how social network theory and research contribute to disease prevention and control; methodological issues that affect recall and agreement when conducting social network studies; how social networks structure and facilitate or discourage health risk; and the role of network ties in disease prevention. The volume concludes by examining the influence of social support in health promotion, symptom identification and disease management.